Penicillium citrinum CFAM 521 Isolated From the Amazon Region: A Novel Source of a Fibrinolytic Enzyme - Thayana Cruz de Souza; Marcos Gustavo Araujo Schwarz; Daniela Marinho da Silva; Carolina Rabelo Maia; Cláudia Patrícia Mendes de Araújo; Antônio Alcirley da Silva Balieiro; Luiz Antonio de Oliveira; Wim Maurits Sylvain Degrave; Ormezinda Celeste Cristo Fernandes; Leila Mendonça-Lima (International Journal of Microbiology)
Fibrinolytic agents are essential in treating thrombosis, playing a critical role in improving survival rates in cardiovascular diseases. Microbial fibrinolytic proteases have emerged as promising alternatives due to their affordability, specificity, lower toxicity, and reduced side effects. Consequently, the search for microorganisms capable of producing these enzymes has gained significant economic importance in the pharmaceutical industry. This study reports and characterizes a novel fibrinolytic enzyme produced by Penicillium citrinum CFAM 521, a strain isolated from the Amazon region. The enzyme was purified using a polyethylene glycol (PEG)–phosphate salt aqueous two-phase system (ATPS). The effects of PEG molecular weight, PEG concentration, and phosphate concentration on the protease partition coefficient (K) were evaluated through a 22 full factorial design. The enzyme exhibited both fibrinolytic and fibrinogenolytic activities. After partitioning in a two-phase system with 10% (w/w) PEG and 15% (w/w) sodium phosphate, the fibrinolytic proteases were predominantly retained in the salt-rich bottom phase (K = 0.33). The enzyme has a molecular weight of 34 kDa, with optimal pH and temperature at 9°C and 37°C, respectively. Inhibitory analysis confirmed that it is a serine protease, and its activity was enhanced by the addition of Mn2+. Notably, the enzyme exhibited no hemolytic activity. Therefore, P. citrinum CFAM 521 represents a novel source of fibrinolytic enzymes, highlighting its potential as an alternative for the development of thrombolytic agents.